Clinical Observation of Comfort Nursing Combined With Continuous Nursing Intervention After Discharge on Improving Pressure Ulcers, Falls, Quality of Life, and Prognosis in Patients With Intracerebral Hemorrhage - Wang, Ji Min; Liu, Zhen; Liu, Hongxia (Frontiers in Surgery, 2022)
Abstract In this prospective study, we randomly divided 131 patients with intracerebral hemorrhage who met the inclusion criteria into 2 groups. One group received routine nursing during hospitalization, and the "Stroke Prevention Knowledge Manual" was issued before discharge, and was recorded as the control group (n= 61); one group received comfort nursing during hospitalization, and implemented continuous nursing after discharge, and was recorded as the research group (n=70). The indicators we observed were the occurrence of pressure ulcers and falls during the hospitalization of the two groups of patients, and the improvement in neurological function, limb function, quality of life, ability of daily living, and emotional state after intervention. We also compared the disability degree of the two groups 6 months after discharge, the readmission status within 6 months of discharge and the nursing satisfaction after intervention. Our conclusion is that comfort nursing combined with continuous nursing intervention after discharge can effectively reduce the occurrence of pressure ulcers and falls during the nursing period of ICH patients, and contribute to the improvement of their quality of life and prognosis. It is worthy of clinical promotion.